2011
DOI: 10.1111/j.1365-2621.2011.02688.x
|View full text |Cite
|
Sign up to set email alerts
|

Response surface optimisation of spray dryer operational parameters for low‐phenylalanine skim milk powder

Abstract: The aim of this study was to optimise the spray-drying process for low-phenylalanine (low-Phe) milk. Influence of inlet air temperature (100, 150 and 200°C), feed flow rate (5, 10 and 15 mL min )1 ) and air flow rate (400, 600 and 800 L h )1 ) on the solubility, yield, water activity and moisture content (MC) of the milk powder were assessed using response surface methodology. The following optimum process parameters were determined: inlet air temperature of 160°C, feed flow rate of 8 mL min )1 and air flow ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Water activity increases with decreasing of the inlet temperature (Table 3). These findings agrees with reported by Amiri-Rigi et al (2011) who determined that inlet air temperature and feed flow rate affected water activity significantly (p < 0.001). Fig.…”
Section: Water Activitysupporting
confidence: 95%
“…Water activity increases with decreasing of the inlet temperature (Table 3). These findings agrees with reported by Amiri-Rigi et al (2011) who determined that inlet air temperature and feed flow rate affected water activity significantly (p < 0.001). Fig.…”
Section: Water Activitysupporting
confidence: 95%
“…In the present study, the yield of powder was 72.07%. Due to the higher total electric charge of the small particles and their light weight, the stickiness of these particles to the instrument wall and the removal of them through the vacuum line increase (Prinn et al ., ; Amiri‐rigi et al ., ). In this study, the size of particles was measured 3.5 ± 1.14 μm, which was fine enough to be lost by the reasons described above.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the relatively low solubility of the powder helps to its low absorption in the upper gastrointestinal tract and decreases the interfering effect of released Fe 2+ on other cationic minerals in the small intestine. It has been reported that high temperatures result in higher solubility of powders due to decreased cohesion rates (Amiri‐rigi et al ., ). However, in this study, in addition to high temperature, the use of HACS limited the powder solubility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…p values < .05 were considered statistically significant for all comparisons. Values were reported as mean ± standard deviation ( SD ) of duplicate treatments (six repetitions for each formula) (Amiri‐Rigi, Mohammadifar, Emam‐Djomeh, & Mohammadi, ).…”
Section: Methodsmentioning
confidence: 99%